Characteristics of human synovial fibroblast activation by IL-1 beta and TNF alpha. - Gitter, B D (1989)
Human synovial fibroblast cell lines (HSN), established from tissues obtained from the knee joints of arthritis patients undergoing arthoplasty, were used to investigate the effects of human interleukin-1 (IL-1) beta and tumour necrosis factor (TNF)alpha on proliferation and prostaglandin E2 (PGE2) secretion. IL-1 beta and TNF alpha were equipotent stimulators of HSN proliferation. Classical non-steroidal anti-inflammatory drugs and glucocorticoids significantly augmented this effect. In addition, IL-1 beta and TNF alpha were potent inducers of PGE2 production while exogenous PGE2 was growth inhibiting. These data suggest that the secretion of PGE2 by monokine-stimulated HSN exerts a negative feedback signal. Further examination of IL-1 beta- and TNF alpha-induced PGE2 secretion revealed IL-1 beta to be a more potent stimulator; however, this observation may be due, in part, to differences in the kinetics of induction. Rabbit anti-IL-1 beta and anti-TNF alpha specifically neutralized both proliferation and PGE2 production induced by these monokines, but anti-IL-1 beta (or anti-IL-1 alpha) did not block TNF alpha activity. It is unclear whether TNF alpha stimulates HSN to produce IL-1, but the antibody data suggest that extracellular IL-1 is not responsible for TNF alpha in vitro activity.